Subaltern Women in The Novel Sing, Unburied, Sing by Jesmyn Ward - Muhammad Dandi Saputra; Muhd. Al-Hafizh (English Language and Literature, 2023)
This research is an analysis of the novel “Sing,Unburied,Sing" by Jasmyn Ward (2017).  In this study, the author aims to reveal the issue of the subaltern woman faced by Leonie’s characters as women who experience subaltern positions in their family and society.  In this analysis, there are two forms of oppression as an part of subaltern women.  The first is verbal oppression such as shouted, being sworn, humiliated, and threatened with harm. This action puts a woman in a subaltern position. The second is physical oppression such as being kicked, hit, pushed, scratched, or pinched.  Physical oppression gives a wound or scar to the woman as a result of the act. This analysis uses the concept of "subaltern, “ a branch of feminism proposed by Gayatri Chakravorty Spivak and supported by several other experts. The use of concepts based on the context of the novel and interpretation of the text.  In this analysis, the elements of the novel that help reveal the subaltern toward women are character, setting, plot, and conflict.